“I want to live at my own pace.” : A study of lifestyle migrants’ motivations to relocate to Onomichi, Hiroshima - Korteniemi, Reetta-Liisa (My University, 2023)
Lifestyle migration and rural depopulation have been gaining more attention in both academic research and media spheres as Japan’s cities and towns are rapidly aging. Additionally, the concept of ikigai has been discussed in greater detail in both academic research and media as people are searching for their own way of living. In contemporary Japan, discourses on gender roles and masculinity have been gaining more traction and many young people are rejecting the old employment norms such as lifetime employment, whether it’s due to their own volition, or due to the pressure and competition stemming from the higher education system of Japan. This thesis is focused on the topics of lifestyle migration and ikigai in the case of the city of Onomichi, located in Hiroshima prefecture. Onomichi has managed to attract many new migrants from all over Japan with the help of the local non-profit organization Onomichi Akiya Saisei Project, that is aiming to renovate old, abandoned buildings (akiya) and bring in new residents and businesses. The city can bring many new insights to the topics discussed in this thesis due to the large number of abandoned properties within its borders. The research was carried out by semi-structured interviews conducted in an online setting during May of 2021. The three informants, males with ages ranging from 28 to 43, are residing in Onomichi and relocated there in hopes of creating a more stress-free lifestyle for themselves. Coincidentally, all of the informants ended up being male, giving this thesis a perspective of the Japanese male and the expectations society imposes on them. Using Onomichi and the informants as a case study, this thesis aims to bring new insights to how lifestyle migrants negotiate their new lives after relocating and how they perceive themselves among the residents of the city. Lifestyle migrants in Onomichi find their new lives to be more fulfilling, albeit filled with more social obligations. They have rejected a corporate lifestyle and are instead working as entrepreneurs, emphasizing that they want to “live life for themselves”. Work and leisure have become more intertwined for the migrants, but this is not always seen as a negative matter. In Onomichi’s case, the migrants described having too much free time on their hands.
Keywords: Japan, lifestyle migration, ikigai, masculinity, rural depopulation